(3QSGdI aj PcQ GdbGQhQI hCMhGdgG hPcQ GdGSJOdGd HgG Ydi GdeRGL GdEfSGfis - (3CHhHcQ GdQGRj , eMeO Hf RcQjG, CHh HcQ GdQGRj,J (B311 (3g` s ((3CMeO Hf TaGFi GdWHjH s)
(3ChdgG (B:s
(3GdMeO ddg hGgH GdYbd hbO hLOJc CSYOc Gddg , eJYLHkG ef JQc LGdjfhS EaQGO cJGH eSJbUi aj PcQ GdHhd , hEZaGd GdMcje HbQGW Pdc s
(3BNQgG (B:s
(3YQhbge ai GdfHV YXjeI dcKQI MQGQJge, hMQcGJ YQhb Scf GdHdGO GdMGQI cGdRfhL hGdfhHI, eJZjQI, dGfHJGJ GdbhI hbdbgG s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B106 s
(3eUOQ GbJfGA GdCUd (B:s
(3cJGHNGfI eQcRj (B- (3LGeYI WgQGf (B(1435) s
Keywords: (3GdWHs